Cycling of oxyanion-forming trace elements in groundwaters from a freshwater deltaic marsh. (1st May 2018) - Telfeyan, Katherine; Breaux, Alexander; Kim, Jihyuk; Kolker, Alexander S.; Cable, Jaye E.; Johannesson, Karen H.
Abstract: Pore waters and surface waters were collected from a freshwater system in southeastern Louisiana to investigate the geochemical cycling of oxyanion-forming trace elements (i.e., Mo, W, As, V). A small bayou (Bayou Fortier) receives input from a connecting lake (Lac des Allemands) and groundwater input at the head approximately 5 km directly south of the Mississippi River. Marsh groundwaters exchange with bayou surface water but are otherwise relatively isolated from outside hydrologic forcings, such as tides, storms, and effects from local navigation canals. Rather, redox processes in the marsh groundwaters appear to drive changes in trace element concentrations. Elevated dissolved S(-II) concentrations in marsh groundwaters suggest greater reducing conditions in the late fall and winter as compared to the spring and late summer. The data suggest that reducing conditions in marsh groundwaters initiate the dissolution of Fe(III)/Mn(IV) oxide/hydroxide minerals, which releases adsorbed and/or co-precipitated trace elements into solution. Once in solution, the fate of these elements is determined by complexation with aqueous species and precipitation with iron sulfide minerals. The trace elements remain soluble in the presence of Fe(III)- and SO4 2- - reducing conditions, suggesting that either kinetic limitations or complexation with aqueous ligands obfuscates the correlation between V and Mo sequestration in sediments with reducing or euxinic conditions.